The Effective and Safe Way to Use Crusade Microcatheter-Facilitated Reverse Wire Technique to Solve Bifurcated Lesions with Markedly Angulated Target Vessel - Jingang Cui; Xiaowei Jiang; Shubin Qiao; Lijian Gao; Jiansong Yuan; Fenghuan Hu; Weixian Yang; Runlin Gao (Journal of Interventional Cardiology)
Objectives. We aim to present a new way to introduce reverse wire in crusade microcatheter-facilitated reverse wire technique to solve markedly angulated bifurcated lesions. Background. Markedly angulated coronary bifurcation lesions are still one of the considerable challenges of treatment with percutaneous coronary intervention especially with severe proximal stenosis. Microcatheter-facilitated reverse wire technique improved the efficacy of crossing a guide wire to such an extremely angulated complex targeted vessel. However, there has been a debate regarding what kind of curve was the best to introduce reverse guide wire in this technique. Methods. We analyzed 7 patients who were admitted to Fuwai Hospital and underwent antegrade wiring which failed. Crusade microcatheter-facilitated reverse wire technique with simple short tip one round curve was used successfully to solve in all 7 bifurcation lesions. We investigated the bifurcation lesion’s characteristics and details of the reverse wire technique procedures. Results. All 7 bifurcations exhibit both a smaller take-off angle and a larger carina angle and severe proximal significant stenosis. After having suitable size of balloon predilation, reverse wire with simple short distal one curve was delivered to distal segment of targeted vessel successfully. We performed all PCI procedures without any complications and no major adverse cardiac event was observed during hospitalization. Conclusions. In solving markedly angulated bifurcated lesions, especially with severe proximal stenosis, crusade microcatheter-facilitated reverse wire technique with simple short tip one curve is an effective and safe way of wiring.